The Effect of Price, Location, Promotion and Service on Purchasing Decisions at CV Anugerah Kirana Motor Bengkulu - Noviantoby Noviantoby; Neri Susanti; Restu Hidayah (Penerbit Jurnal Indonesia, 2023)
CV. Anugrah Kirana Motor Bengkulu is an official dealer of Honda Motorcycle. The address of this dealer is at Dempo Street 18, Sawah Lebar, Ratu Agung, Bengkulu. This dealer sells some kinds of motorcycle types like Honda Scoopy, Honda Vario, Honda Beat and other kinds of motorcycle. The research objective is to determine the influence of price, promotion location and service on purchasing decisions at CV Anugerah Kirana Motor Bengkulu. The sample in this study are 80 consumers who purchased automatic type motorbikes at CV Anugerah Kirana Motor Bengkulu. Data are collected by using a questionnaire and analyzed by using multiple linear regression and hypothesis testing. The results of multiple linear regression calculations obtained multiple linear regression equations Y = 12.106 + 0.356 X1 + 0.249 X2 + 0.372 X3 + 0.132 X4 + e. The results of the t-test variable Price (X1) have a positive and partially significant effect on purchasing decisions with a significant value of 0.022 < 0.05. The location variable (X2) has a partially positive and significant effect on purchasing decisions with a significant value of 0.016 <0.05. The promotion variable (X3) has a positive and partially significant effect on purchasing decisions with a significant value of 0.027 <0.05 and the service variable (X4) has a positive and partially significant effect on purchasing decisions with a significant value of 0.008 <0.05. The results of the F test significance value of 0.000 is less than 0.05 (<0.05), this indicates that simultaneously (simultaneously) there is a significant influence between price, location, promotion and service on purchasing decisions at CV Anugerah Kirana Motor Bengkulu. price variable (X1) location (X2) promotion (X3) and service (X4) have a positive and significant effect on purchasing decisions.